Pemanfaatan Limbah Ban Bekas untuk Sintesis Nanokomposit MnO2/C dengan Metode Hidrotermal sebagai Material Superkapasitor - Adithia, Rizky Putra; Muckharom, Ahmad Ali; Ditalistya, Tabah; Karimah, Putri Diah Wahyu; Efiyanti, Lisa; Subagio, Agus (Universitas Andalas, 2024)
Activated carbon from waste tires is used as MnO2 metal oxide doping in making MnO2/C-based nanocomposites into high-density and environmentally friendly supercapacitor electrodes. The MnO2/C nanocomposite synthesis process was carried out using the hydrothermal method by varying the mass of activated carbon by 1.25 g, 2.5 g and 3.75 g to determine the optimum results. Based on the results of research that has been carried out, it shows that MnO2/C can be used as a high density supercapacitor electrode. This is in accordance with the XRD test results which show that the MnO2 nanocomposite with the addition of C was successfully synthesized and has an orthorhombic crystalline phase. The SEM test results show that the material has almost the same morphology, namely many protrusions which make each particle have high roughness. The most optimal results were obtained from the MnO2/C-50 variation because it has the highest C element content, namely 39.93%, so it has the highest capacitance value of 5.791 f/g during the CV test. The GCD test shows that electrodes with a carbon variation of 2.5 g have a much longer and constant charge-discharge measurement time. In the EIS test, this variation shows a resistance value that is not too high and not too small, materials that have good storage capacity or capacity have moderate resistance.